The Endometriosis - treatment and new methods - Jakub Chrzanowski; Sandra Ostaszewska; Kinga Augustynowicz; Ewa Szymańska; Kinga Świąder (Kazimierz Wielki University, 2023)
Introduction: Endometriosis is a common disease, especially in young women. In this article, we reviewed the epidemiology, symptoms, and various options for the treatment of endometriosis. Material and methods: The work was based on medical articles collected in PubMed, websites and medical books. The research was conducted by looking at keywords such as: "endometriosis", "endometriosis treatment", "endometriosis and new methods" Results: There are many methods of treating endometriosis, ranging from hormonal therapy to surgical treatment. Conclusions: Endometriosis is difficult disease to treat. We need more researches and experience to find the perfect way treatment without side effects.